AIDS prevention practices among dental clinicians - Flores, Jocelyn Hilario (The Journal of the Philippine Dental Association)
Awareness is not enough as far as danger and spread of AIDS is concerned. Health providers, educators, administrators, and researchers must internalize the etiology, mode of transmission, education and prevention of this infection.